IgA nephropathy with crescent cell lesions in a human brucellosis patient: a case report - Qi, Dongli; Yu, Ricong; Wan, Qijun; Xu, Yi (Frontiers in Nephrology, 2025)
Brucellosis is known to impact multiple organ systems in humans, including the urogenital system; however, the occurrence of glomerular diseases is relatively uncommon. In this study, we present the case of a 45-year-old man with no prior history of renal disease who developed gross hematuria, proteinuria, acute kidney injury, anemia, hypoproteinemia, pleural effusion, arthralgia, and lymphadenopathy following an acute Brucella infection. Renal biopsy revealed mesangial proliferative immunoglobulin A (IgA) nephropathy with partial crescents, classified as M1E0S0T0C2 according to the Oxford classification, in conjunction with Brucella spondylitis. The patient achieved complete remission after 4 months of anti-brucellosis therapy with doxycycline, levofloxacin, and rifampicin. In this paper, we present a case study of IgA nephropathy complicated by cellular crescent lesions resulting from acute Brucella infection, which completely resolved following anti-Brucella therapy. In addition, we review previously documented cases of Brucella-associated glomerular disease confirmed through renal biopsy, aiming to offer a reference for clinical diagnosis and treatment.